2009
DOI: 10.1105/tpc.109.070060
|View full text |Cite
|
Sign up to set email alerts
|

ARABIDOPSIS TRITHORAX-RELATED7 Is Required for Methylation of Lysine 4 of Histone H3 and for Transcriptional Activation of FLOWERING LOCUS C    

Abstract: In the winter-annual accessions of Arabidopsis thaliana, presence of an active allele of FRIGIDA (FRI) elevates expression of FLOWERING LOCUS C (FLC), a repressor of flowering, and thus confers a vernalization requirement. FLC activation by FRI involves methylation of Lys 4 of histone H3 (H3K4) at FLC chromatin. Many multicellular organisms that have been examined contain two classes of H3K4 methylases, a yeast (Saccharomyces cerevisiae) Set1 class and a class related to Drosophila melanogaster Trithorax. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
174
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 80 publications
8
174
2
3
Order By: Relevance
“…These findings suggest that histone methylation may play broad and important roles in regulating transcription. Consistent with this notion, several Arabidopsis histone methyltransferase (HMTase) mutants have been found to exhibit a myriad of developmental abnormalities (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Furthermore, transcriptome profiling studies have identified numerous genes that are misregulated in HMTase mutants (19,27,28).…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…These findings suggest that histone methylation may play broad and important roles in regulating transcription. Consistent with this notion, several Arabidopsis histone methyltransferase (HMTase) mutants have been found to exhibit a myriad of developmental abnormalities (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Furthermore, transcriptome profiling studies have identified numerous genes that are misregulated in HMTase mutants (19,27,28).…”
mentioning
confidence: 61%
“…This largely reflects the fact that the major H3K4me3 HMTase has yet to be identified. Mutants in three of the seven class III HMTase genes (ATX1/SDG27, ATX2/SDG30, ATXR7/SDG25) display locus-specific defects in H3K4me; however, the global levels of H3K4me3 in these mutants remain similar to that of wild type (25,26,28,35).…”
mentioning
confidence: 94%
“…Local chromatin states are critical for quantitatively controlling FLC expression (9). Active FLC expression requires functional FRIGIDA (FRI) and a set of histone modifying Trithorax homologs, Complex Proteins Associated with Set1 (COMPASS), RNA polymerase II Associated Factor 1 complex (PAF1C), and SET DOMAIN GROUP 8 (SDG8), the major H3K36 methyltransferase (10)(11)(12)(13)(14)(15)(16)(17). Repression of FLC requires either the autonomous pathway, which coordinately influences transcriptional initiation and elongation with associated chromatin modulation, or vernalization, the cold-induced Polycomb silencing (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…ATXR7 is a Set1-related H3K4 methyltransferase that acts in combination with ATX1 to regulate various processes, for example, flowering (Tamada et al, 2009).…”
Section: Histone Methylasesmentioning
confidence: 99%